Analisis Hukum Waris Islam Dalam Konteks Kesetaraan Gender Dan Perlindungan Hak Perempuan - Masrofah Masrofah; Yusuf Bagus Febrianto; Kanda Reza Pahlevi Tetuko Mozaik Romadhona (Journal of Innovative and Creativity, 2026)
The discourse on Islamic inheritance law is often linked to the issue of gender equality, particularly regarding the distribution of inheritance in which men receive twice the share of women, and is therefore frequently perceived as unjust. Such assessments, however, often fail to fully consider the historical background and social context in which Islamic inheritance law emerged—a context in which it represented a progressive reform from pre-Islamic traditions that denied women any inheritance rights. This study aims to analyze Islamic inheritance law from the perspective of gender equality and the protection of women's rights, as well as to evaluate its implementation within Indonesian Muslim society. The research adopts a normative juridical method with a descriptive qualitative approach, examining legal norms, doctrines, and social data. The findings indicate that although Islamic legal texts stipulate a 2:1 inheritance ratio between men and women, this provision is not inherently discriminatory but rather reflects a proportional distribution of socio-economic responsibilities at the time. However, in the context of modern society, there exists a degree of implementation flexibility that allows for family deliberation and adaptation to gender equality principles, ensuring that Islamic inheritance law remains relevant and just within a dynamic social framework.